A study on the level of written and oral apprehensions of undergraduates in NTU and NUS. - Chen, Yan Ling. (2008)
This project wishes to go into depth an exploratory study on the levels of written and oral communication apprehensions of undergraduates in Nanyang Business School (NTU) and Business Administration (NUS).